Detection of fruit deterioration biomarkers on fresh-cut pineapple via gene expression assay based on electrochemical biosensor - Kaewdee , Mallika; Chaumpluk, Piyasak (Journal of Postharvest Technology, 2017)
A technique for the semi-quantitative determination of target deterioration markers through gene expression in tissues of fresh cut pineapple based on electrochemical biosensor was developed. This method employed RT-PCR amplification of a specific domain corresponding to a target ATP synthase, polyphenol oxidase, superoxide dismutase gene and a common housekeeping 18S rRNA gene, and a phenomenon of DNA aggregation induced by Hoechst 33258 in conjunction with changes in anodic current peaks measured via a carbon screen printed electrode on linear sweep voltammetry. Anodic current peaks of the resulting cDNA products from pineapple tissues during storage were between 1.16-2.35 µA. Semi-quantitative analysis for the level of deterioration markers through gene expression was measured using the comparative ratio between copy numbers of target gene and housekeeping 18S rRNA genes. The expression of ATP synthase, polyphenol oxidase, superoxide dismutase gene at 25 oC was detected as early as 6 hours after storage. SOD expression level having more abundance than the rest studied might play key role in quality deterioration in pineapple. Semi-quantitative studies on gene expression revealed the increase in patterns of gene expression especially that of SOD up to 89.14% comparing with that of a housekeeping gene. These results provided gene expression configuration in responding to postharvest conditions of fresh cut pineapple. The technique has several merits on its rapidity and simplicity in quantifying gene expression. This is also a cost effective technique since no sophisticated devices and expensive reagents are needed.